دور المصارف الإسلامية في تنشيط قطاع التجارة في سورية دراسة ميدانية على بنك سورية الدولي الإسلامي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تتميز المصارف الإسلامية عن غيرها من المصارف بأنها مؤسسات مالية واقتصادية واجتماعية تسعى لتشجيع الاستثمار, وجعل العمل شريكاً أساسياً لرأس المال ومصدراً للكسب الحلال, وتسهم في عملية التنمية الاقتصادية من خلال ما تقوم به من المرابحة أو المضاربة أو المشاركة, وبالتالي تحقيق قدر كبير من تنمية القطاعات التي يسعى المستثمرون إلى تأسيسها. يتناول البحث دور المصارف الإسلامية في تنشيط قطاع التجارة في سورية من خلال دراسة ميدانية على بنك سورية الدولي الإسلامي, حيث تمّ تطبيق استبانة على عينة من العاملين في البنك بلغت /131/ عاملاً , وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: - يسهم بنك سورية الدولي الإسلامي في دعم أنشطة التجارة من خلال: دفع حصيلة الصادرات, منح كفالات مصرفية, تقديم خدمة الاعتمادات المستندية للمصدرين والمستوردين, دعم أنشطة القطاع الصناعي, تعزيز التعاون التجاري والاقتصادي بين سورية والدول العربية. - إن دور بنك سورية الدولي الإسلامي في دعم أنشطة القطاع الزراعي (مشاريع الري واستصلاح الأراضي, إنشاء نقاط المياه وحفر الآبار), والاستثمار المباشر في مشروعات معدة للتصدير ما يزال محدوداً. - يسهم بنك سورية الدولي الإسلامي في توفير التسهيلات اللازمة للمبادلات التجارية بين الدول العربية عن طريق تشجيع التبادل السلعي فيما بينها. Islamic banks are financial institutions that seek to encourage investment, and make work a key partner for capital and a source of gain from it, and contribute to the economic development process through its speculation or participation, and thus achieve a great deal of development sectors sought by investors to its foundation. The research addresses the role of Islamic banks in promoting the trade sector in Syria through a field study on the Syrian International Islamic Bank, which was applied to identify a sample of employees in the bank amounted to / 131 / Agent. After study and analysis, it reached following results: - Syria International Islamic Bank contributes in supporting the trade activities through: paying the proceeds of exports, granting bank guarantees, documentary credits provide a service to exporters and importers, supporting the activities of the industrial sector, and promoting the trade and economic cooperation between Syria and Arab countries. - The role of the Syrian International Islamic Bank is supporting the activities of the agricultural sector (irrigation, land reclamation, the establishment of water points and wells), and direct investment in projects for export is still limited. - Syria International Islamic Bank contributes in providing the necessary facilities for trade between Arab countries through the promotion of commodity exchange between them.